Inside Back Cover: Selective Targeting of Tumor and Stromal Cells By a Nanocarrier System Displaying Lipidated Cathepsin B Inhibitor (Angew. Chem. Int. Ed. 38/2014). Issue 38 (22nd July 2014) - Mikhaylov, G.; Klimpel, D.; Schaschke, N.; Mikac, U.; Vizovisek, M.; Fonovic, M.; Turk, V.; Turk, Boris; Vasiljeva, Olga
<x xml:space="preserve">Abstract</x> A drug‐delivery system that targets cancer‐associated extracellular cathepsin B is described by B. Turk, O. Vasiljeva, et al. in their Communication on page 10077 ff. The developed system is based on a lipidated cathepsin B‐specific inhibitor incorporated into the envelope of the liposomal nanocarrier, which could be used for selective targeting of tumor and stroma cells in the microenvironment of the tumor, while sparing the healthy normal cells.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>